A study on the pathways and their interannual variability of the Fukushima-derived tracers in the northwestern Pacific - Kim, Sang-Yeob; Lee, Ho Jin; Jung, Kyung Tae; Kim, Haejin; Kim, Kyeong Ok (Frontiers in Marine Science, 2024)
This study investigates that the subsurface pathways, travel time, and its interannual variability of Fukushima-derived tracers subducted with the North Pacific subtropical mode water (NPSTMW) using 22-year-long (1994-2015) eddy-resolving (1/12) and eddypermitting (1/4) ocean reanalysis. The NPSTMW is a thick subsurface layer with low potential vorticity and relatively uniform potential density, making it a key indicator of the North Pacific oceanic conditions. A series of Lagrangian particle tracking simulations quantitatively revealed that the Fukushima-derived particles moved along the Kuroshio Extension (KE) and spread over the majority of the subtropical region in the northwestern Pacific within 4-5 years.Approximately 36% of the particles flowed eastward in the Kuroshio-Oyashio transition zone (KO) and thereafter re-emerged to the sea surface at the remote area (near dateline), and 30% of particles moved along the KE. The remaining 34% subducted into NPSTMW layer and then widely spread out to the subtropical region along the re-circulation gyre (RG), exhibiting a subsurface pathway during entire particle tracking. When the particles were released, their pathway was immediately determined, whether it flowed along the KO (>36N), KE (30-36N), or RG (<30N). Furthermore, the interannual variability of the pathways was significantly associated with the dynamic states of KE, such as the path length of the Kuroshio jet. This result implies that understanding the subsurface dynamics and its variability of the KE and NPSTMW is crucial for predicting the dispersion of radioactive materials in the subsurface layer and its potential impact.